Innovation and Adaptation of Islamic Religious Education in Madrasahs in the Context of Society 5.0 Era - Zainuddin, Zainuddin; Abidin, Zaenal; Susanti, Anis; Muttaqin, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Society 5.0 era presents challenges and opportunities for Islamic religious education in madrasas. This study aims to analyze the innovations and adaptations needed to face this era. Using a qualitative method with a Library Research approach and content analysis, this study examines various related literature sources. The results show that the main challenges include limited technological infrastructure and lack of human resource readiness. Many madrasahs still rely on traditional methods and show resistance to change. In conclusion, a comprehensive strategy is needed, including infrastructure improvement, teacher digital competency development, curriculum update, and mindset change. Recommendations include technology training programs, collaboration with the technology sector, and education policy reforms to support digital transformation in madrasahs